A Coevolved EDS1-SAG101-NRG1 Module Mediates Cell Death Signaling by TIR-Domain Immune Receptors. Issue 10 (16th July 2019) - Lapin, Dmitry; Kovacova, Viera; Sun, Xinhua; Dongus, Joram A.; Bhandari, Deepak; von Born, Patrick; Bautor, Jaqueline; Guarneri, Nina; Rzemieniewski, Jakub; Stuttmann, Johannes; Beyer, Andreas; Parker, Jane E.
Abstract : TNL-activated cell death in response to bacterial effectors in Arabidopsis and Nicotiana benthamiana involves a coevolved module of helper NLR NRG1 with the lipase-like proteins EDS1 and SAG101. Abstract: Plant nucleotide binding/leucine-rich repeat (NLR) immune receptors are activated by pathogen effectors to trigger host defenses and cell death. Toll-interleukin 1 receptor domain NLRs (TNLs) converge on the ENHANCED DISEASE SUSCEPTIBILITY1 (EDS1) family of lipase-like proteins for all resistance outputs. In Arabidopsis ( Arabidopsis thaliana ) TNL-mediated immunity, At EDS1 heterodimers with PHYTOALEXIN DEFICIENT4 ( At PAD4) transcriptionally induced basal defenses. At EDS1 uses the same surface to interact with PAD4-related SENESCENCE-ASSOCIATED GENE101 ( At SAG101), but the role of At EDS1- At SAG101 heterodimers remains unclear. We show that At EDS1- At SAG101 functions together with N REQUIRED GENE1 ( At NRG1) coiled-coil domain helper NLRs as a coevolved TNL cell death-signaling module. At EDS1- At SAG101- At NRG1 cell death activity is transferable to the Solanaceous species Nicotiana benthamiana and cannot be substituted by At EDS1- At PAD4 with At NRG1 or At EDS1- At SAG101 with endogenous Nb NRG1. Analysis of EDS1-family evolutionary rate variation and heterodimer structure-guided phenotyping of At EDS1 variants and At PAD4- At SAG101 chimeras identify closely aligned ɑ-helical coil surfaces in the At EDS1- At SAG101 partner C-terminal domains that are necessary for reconstituted TNL cell death signaling. Our data suggest that TNL-triggered cell death and pathogen growth restriction are determined by distinctive features of EDS1-SAG101 and EDS1-PAD4 complexes and that these signaling machineries coevolved with other components within plant species or clades to regulate downstream pathways in TNL immunity.